Images of Tatars by K.F. Huhn in periodicals of the second half of the 19th century - Dina F. Gatina-Shafikova (Историческая этнология, 2025)
Since the 18th century, Russia has seen a growing interest in the ethnography and culture of peoples, which was reflected in publications in periodicals. Artists, such as Karl Fyodorovich Huhn (1831–1877), took an active part in the creation of illustrations reflecting the life and traditional costumes of various peoples, including the Tatars. K.F. Huhn, known for his watercolors and engravings, accurately conveyed details of costumes and daily life, which makes his works an important historical source. The master’s works were published in Russian and foreign periodicals, such as the magazines Niva, Picturesque Review, World Illustration, and the German illustrated sheet Münchener Bilderbogen. Not only exact copies of Karl Fyodorovich’s watercolors were published, but also the artist himself created collages combining various subjects. His works were often reprinted and were included in ethnographic collections. Four engravings based on his images were published in the Niva magazine from 1875 to 1887, and three more were published in Zhivopisnoye Obozreniye and Vsemirnaya Illustratsiya. In Münchener Bilderbogen, K.F. Huhn prepared two illustrated sheets that later became prototypes for Russian publications. A study of the graphic works of the artist K.F. Huhn showed that they not only reflect the cultural and historical aspects of Tatars’ life, but also demonstrate the evolution of folk costume and artistic style. His legacy includes oil paintings, pencil sketches, watercolors, engravings and lithographs, which continue to be a valuable source for the study of ethnography and art of the 19th century.